2018
DOI: 10.1186/s13048-018-0458-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-1290 is a potential biomarker of high-grade serous ovarian carcinoma and can discriminate patients from those with malignancies of other histological types

Abstract: BackgroundmicroRNAs (miRNAs) stably exist in circulating blood encapsulated in extracellular vesicles such as exosomes; therefore, serum miRNAs have the potential to serve as novel cancer biomarkers. New diagnostic markers to detect high grade serous ovarian cancer (HGSOC) are urgently needed. The aim of this study was to identify miRNAs specific to HGSOC and analyze whether serum miRNA can discriminate HGSOC patients from healthy controls or patients with ovarian malignancies of other histological types.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 31 publications
0
56
0
Order By: Relevance
“…Kobayashi et al have shown significant overexpression of serum miR-1290 in advance stage HGSOC in comparison to early stage. Moreover, it was capable to discriminate patients with HGSOC from patients with malignancies of other histological subtypes with a sensitivity of 47% and specificity of 85% (AUC = 0.76), thus reflecting diagnostic potential of miR-1290 for HGSOC (Kobayashi et al, 2018).…”
Section: Chemoresistancementioning
confidence: 94%
“…Kobayashi et al have shown significant overexpression of serum miR-1290 in advance stage HGSOC in comparison to early stage. Moreover, it was capable to discriminate patients with HGSOC from patients with malignancies of other histological subtypes with a sensitivity of 47% and specificity of 85% (AUC = 0.76), thus reflecting diagnostic potential of miR-1290 for HGSOC (Kobayashi et al, 2018).…”
Section: Chemoresistancementioning
confidence: 94%
“…Here, we identified a new hypoxia-associated miRNA, miR-1290, which promotes cell migration and invasion of cancer cells [69,70]. In addition, EV miR-1290 was found to be a biomarker in ovarian carcinoma [71]. MiR-1290 was not detected or had a very low expression in nEVs, normoxic and hypoxic whole cell lysates (data not shown), which means that this miRNA is specifically loaded into hEVs.…”
Section: Discussionmentioning
confidence: 94%
“…Deb et al summarized the current knowledge regarding the role of miRNA expression in OC [27]. In addition, several previous studies have shown that stable circulating miRNAs play an increasingly important role in the diagnosis of OC [9][10][11][12][13][14][15]. However, to our knowledge, few reports have described miRNA levels in exosomes isolated from the plasma of OC patients [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%